2019
DOI: 10.1186/s12882-019-1548-y
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide ameliorates renal injury in a pristane-induced lupus mouse model by modulating Th17/Treg balance

Abstract: Background Lupus nephritis (LN) is an inflammation of the kidneys and is a major cause of mortality in systemic lupus erythaematosus (SLE) patients. In addition, Th17/Treg balance is one of the most important factors that can promote the development of LN. It has been reported that vasoactive intestinal peptide (VIP) is associated with the downregulation of both inflammatory and autoimmune diseases through regulating T lymphocyte balance. Therefore, the aim of this study was to determine the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(27 reference statements)
2
18
0
Order By: Relevance
“…This claim is supported by numerous experimental studies in both animal models and ex vivo samples of patients [5,[155][156][157][158]. VIP was able to decrease the cytokine profile and master regulators related to Th1 and Th17 subsets and to increase those of them related to Treg or Th2 in different autoimmunity animal models, such as the collagen-induced (CIA) arthritis mouse model of RA, the TNBS mouse model of Crohn's disease, the nonobese diabetic (NOD) mouse model of autoimmune diabetes, the experimental autoimmune encephalomyelitis (EAE) mouse model of multiple sclerosis, the experimental model of autoimmune myocarditis, and the pristine-induced lupus model of lupus nephritis [7,11,[159][160][161][162][163][164][165]. In addition, this immunomodulatory role of VIP was observed in two inflammatory animal models, including the models of CNS inflammation or atherosclerosis [108,164].…”
Section: Regulating Th Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This claim is supported by numerous experimental studies in both animal models and ex vivo samples of patients [5,[155][156][157][158]. VIP was able to decrease the cytokine profile and master regulators related to Th1 and Th17 subsets and to increase those of them related to Treg or Th2 in different autoimmunity animal models, such as the collagen-induced (CIA) arthritis mouse model of RA, the TNBS mouse model of Crohn's disease, the nonobese diabetic (NOD) mouse model of autoimmune diabetes, the experimental autoimmune encephalomyelitis (EAE) mouse model of multiple sclerosis, the experimental model of autoimmune myocarditis, and the pristine-induced lupus model of lupus nephritis [7,11,[159][160][161][162][163][164][165]. In addition, this immunomodulatory role of VIP was observed in two inflammatory animal models, including the models of CNS inflammation or atherosclerosis [108,164].…”
Section: Regulating Th Cellsmentioning
confidence: 99%
“…VIP not only acts on a specific subset in these pathologies, but is also able to balance the different Th subsets, inducing nonpathogenic phenotypes or modify their plasticity. Studies on different transcription factors, cytokines, cytokine receptors, chemokines, and chemokine receptors in the above mentioned mice models, in vitro or ex vivo, showed that VIP counterbalances the ratio of Th1/Th2, Th17/Treg, Th1/Treg, or Th2/Th9, reducing pathogenicity and increasing tolerance [10,165,168]. Th17 cells are a heterogeneous subset with a nonpathogenic or pathogenic profile, depending on the microenvironment.…”
Section: Regulating Th Cellsmentioning
confidence: 99%
“…Approximately, 60% of patients with proliferative SLE progress to end-stage renal disease, and lupus nephritis (LN) is considered a major cause of mortality in SLE patients. 7 Although the pathogenesis of LN is unclear, defective immune regulatory mechanisms, such as impaired T helper (Th) cell function, including Th1/Th2 and Th17/regulatory T cell imbalance, have been recognized as important contributors to the aetiology of SLE. 8 Proinflammatory cytokines stimulate plasma cells to produce autoantibodies that promote organ damage.…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory T (Treg) cells, characterised by their cell surface markers: CD4, CD25, and Foxp3, are present in the peripheral blood and spleen and mediate remarkable immunosuppressive effects [4,5]. The importance of regulatory T cells in immunoregulation and tolerance development has been well demonstrated [6,13]. Speci cally, the expression of the transcription factor fork head box p3 (Foxp3) determined the development and differentiation of Treg cells [14], and its increase activated CD4 + CD25 + Treg cells in vitro [15].…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally, the expression of the transcription factor fork head box p3 (Foxp3) determined the development and differentiation of Treg cells [14], and its increase activated CD4 + CD25 + Treg cells in vitro [15]. However, the dysregulation of Tregs is a pivotal factor for the development of LN [13], and a pool of Foxp3 + Treg cells has been associated with LN features.…”
Section: Introductionmentioning
confidence: 99%